PERLAKUAN SUAMI TERHADAP ISTRI SAAT NUSHŪZ PERSPEKTIF IMAM AL-HAROMAYN DAN IMAM AL-NAWAWĪ - Maulana, Ahmad In’am; Zaman, Ahmad Zuhairuz (Mabahits : Jurnal Hukum Keluarga Islam, 2025)
Islam requires a husband to provide for his wife physically and spiritually. However, the husband's responsibility depends on the wife's obedience. A wife's behavior of nushūz can result in the loss of her husband's responsibility for providing for her. The issue of nushūz and its legal consequences have been widely debated by Islamic scholars. This study aims to delve deeper into the categories of wives' attitudes during nushūz and explore the concept of how a husband should treat his wife during nushūz from the perspectives of Imam Al-Ḥaromayn and Imam Al-Nawawī. This study uses a library research method with a qualitative approach. The primary data sources are the Nihāyat al-Maṭlab and Minhāj al-Ṭālibīn. Meanwhile, secondary data sources are related books and articles, scientific works, and online sources. The results of the study indicate that Imam Al-Ḥaromayn considers a wife to be nushūz if she leaves the house without permission or refuses an obligation and cannot be guided back. According to Imam Nawawī, nushūz occurs when a wife refuses obligations, such as intimate relations, household responsibilities, or leaving the house without permission. Imam Al-Ḥaromayn argues that a husband should first advise his wife, then leave the bed, and if nushūz continues, the husband can gently hit her without causing injury. Imam Nawawī also recommends advice as a first step, followed by separation from the bed, and light spanking if nushūz continues, provided it is not painful. Imam Al-Ḥaromayn states that nushūz can disrupt marital harmony and may require mediation or legal action, with the husband acting fairly and considering the wife's rights. Imam Nawawī emphasizes advice as the first step, followed by separation from the bed, and light spanking if nushūz recurs, on the principle of justice.